Informing conservation decisions to target private lands of highest ecological value and risk of loss. Issue 5 (30th May 2022) - Hansen, Andrew J.; Mullan, Katrina; Theobald, David M.; Robinson, Nathaniel; East, Alyson; Powell, Scott
Abstract: Natural habitats on private lands are potentially important components of national biodiversity conservation strategies, yet they are being rapidly lost to development. Conservation easements and other means of protecting these habitats have expanded in use and will be most effective if they target private lands of highest biodiversity value and risk of loss. We developed a Biodiversity Conservation Priority Index (BCPI) based on ecological value and risk of habitat loss for remaining areas of natural vegetation cover (NVC) in the northwestern United States and addressed two questions: (1) Which remaining NVC on private lands is the highest priority for biodiversity conservation based on ecological value and risk of development? And (2) are conservation easements in NVC placed preferentially in locations of high biodiversity conservation priority? Drawing on the concept of ecological integrity, we integrated five metrics of ecological structure, function, and composition to quantify ecological value of NVC. These included net primary productivity, species richness, ecosystem type representation, imperiled species range rarity, and connectivity among "Greater Wildland Ecosystems." Risk of habitat loss was derived from analysis of biophysical and sociodemographic predictors of NVC loss. Ecological value and risk of loss were combined into the BCPI. We then analyzed spatial patterns of BCPI to identify the NVC highest in biodiversity conservation priority and examined the relationship between BCPI and conservation easement status. We found that BCPI varied spatially across the study area and was highest in western and southern portions of the study area. High BCPI was associated with suburban and rural development, roads, urban proximity, valley bottom landforms, and low intensity of current development. Existing conservation easements were distributed more towards lower BCPI values than unprotected NVC at both the study area and region scales. The BCPI can be used to better inform land use decision making at local, regional, and potentially national scales in order to better achieve biodiversity goals.